Proteger: A Social Robotics System to Support Child Psychological Evaluation - Godoi, Diogo; Romero, Roseli; Azevedo, Helio; Ramos, Josué; Beraldo Filho, Germano; Garcia, Márcia Ap. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Human development is characterized by a complex and continuous process marked by systematic changes in several domains throughout the life cycle. Childhood corresponds to the initial stage of this process, constituting a period of intense and important transformations, which will inﬂuence the following the observation stages. Precisely because of of psychological changes in childhood requires diagnosis and treatment by a trained therapists. Due to the child’s reduced capacity to express, or even understand, his feelings or unpleasant experiences that may have happened, the processes of evaluation, forensic expertise and professional diagnosis may face obstacles in the search for accurate information. It is understood that this process involves a set of techniques, such as conducting interviews with parents and educators; observation of the child in the school and residential environment and the ludic contact with the child. Ludic resources gain special prominence in this process and are used to bring the professional closer to the child, facilitating the child’s expression. In this article, we are proposing a collaborative system, called Proteger, which uses a humanoid robot as a ludic resource in the psychological diagnosis process involving children. The developed interface is presented together with all the features available in the system. The teleoperated humanoid robot, with a children’s voice and some basic movements, should help the professional to break the resistance offered by some children to participate in evaluation sessions.